IMPLEMENTASI PERMA NOMOR 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI: (EFEKTIVITAS MEDIASI PADA PERKARA PERCERAIAN DI PENGADILAN AGAMA PALU) - Heru Susanto; Nursyamsu Nursyamsu (Fakultas Syariah Institut Agama Islam Negeri Palu, 2017)
Mediation is one of the means and efforts to resolve disputes that occur between husband and wife in a peaceful manner that is appropriate, effective, and can open wider access to the parties to obtain a satisfactory and just settlement. In response, the Supreme Court release the regulation of supreme court governing mediation procedure in proceedings in court. Beginning with the SEMA (Surat Edaran Mahkamah Agung) or Supreme Court Circular Number 1 year 2002 on the Empowerment of the First Tribunal Applying the Peace Institution, instructed all the judges who tried the case, in order to sincerely seek peace among the litigants. However, because some basic matters have not been explicitly stipulated in the SEMA, the Supreme Court issued Perma (Regulation of the Supreme Court) RI Number 2 Year 2003 on Mediation Procedure in Court, which was then revised and refined by Perma Number 1 Year 2008, which further reinforce the obligation to pursue mediation procedures related to litigation in court. And its peak on February 4, 2016 Supreme Court renewed by ratifying Perma Number 1 Year 2016 on Mediation Procedure. This paper discusses about how the implementation of this Perma, what are the supporting and inhibiting factors in the success of mediation and the extent of its effectiveness in the settlement of divorce cases in the Religious Court of Palu.